Pengaruh Jumlah Penduduk Terhadap Konsumsi Beras di Kecamatan Asparaga Kabupaten Gorontalo - Idrus Ismail (Gorontalo Development Review, 2018)
This study aims to determine the effect of Total Population on Rice Consumption in the District of Asparaga Gorontalo Regency can be fulfilled. The data used in this study Primary data obtained directly from the object of research either through interviews or from the observation (observation) in the community in District Asparaga Gorontalo and secondary data that is sourced from documents in related institutions in District Asparaga Regency Gorontalo. The method of analysis used is simple regression analysis method to see the relation of population to rice consumption with the help of SPSS Program which used in analyzing data.The results obtained from the data that has been collected to obtain the regression equation Y = 601.439 + 0.997 X means the Number of residents in District Asparaga Gorontalo regency in every year very little effectThis study aims to determine the effect of Total Population on Rice Consumption in the District of Asparaga Gorontalo Regency can be fulfilled. The data used in this study Primary data obtained directly from the object of research either through interviews or from the observation (observation) in the community in District Asparaga Gorontalo and secondary data that is sourced from documents in related institutions in District Asparaga Regency Gorontalo. The method of analysis used is simple regression analysis method to see the relation of population to rice consumption with the help of SPSS Program which used in analyzing data.The results obtained from the data that has been collected to obtain the regression equation Y = 601.439 + 0.997 X means the Number of residents in District Asparaga Gorontalo regency in every year very little effect